NFI‐C2 temporal‐spatial expression and cellular localization pattern during tooth formation. (21st December 2015) - Lamani, Ejvis; Gluhak‐Heinrich, Jelica; MacDougall, Mary
Abstract : Currently, little is known regarding critical signaling pathways during later stages of tooth development, especially those associated with root formation. Nfi‐c null mice, lacking molar roots, have implicated the transcription factor NFI‐C as having an essential role in root development. Previously, we identified three NFI‐C isoforms expressed in dental tissues with NFI‐C2 being the major transcript. However, the expression pattern of the NFI‐C2 protein is not characterized. In this study we performed in situ hybridization and immunohistochemistry using isoform specific probes. We show the production of a NFI‐C2 peptide antibody, its characterization, the temporal‐spatial expression pattern of the NFI‐C2 protein during odontogenesis and sub‐cellular localization in dental cells. Moderate NFI‐C2 staining, as early as bud stage, was detected mostly in the condensing dental ectomesenchyme. This staining intensified within the dental pulp at later stages culminating in high expression in the dentin producing odontoblasts. The dental epithelium showed slight staining until cytodifferentiation of enamel organ into ameloblasts and stratum intermedium. During root formation NFI‐C2 expression was high in the Hertwig's epithelial root sheath and later was found in the fully developed root and its supporting tissues. NFI‐C2 cellular staining was cytosolic, associated with the Golgi, and nuclear. These data suggest a broader role for NFI‐C during tooth formation than limited to root and periodontal ligament development. Abstract : Currently, little is known regarding critical signaling pathways during later stages of tooth development, especially those associated with root formation. Nfi‐c null mice, lacking molar roots, have implicated the transcription factor NFI‐C as having an essential role in root development. In this study we show the production of a NFI‐C2 peptide antibody, its characterization, the temporal‐spatial expression pattern of the NFI‐C2 protein during odontogenesis and sub‐cellular localization in dental cells.